Exceptionally preserved ostracodes from a Middle Miocene palaeolake, California, USA - Wilkinson, I; Wilby, P; Williams, M; Siveter, D; Page, A; Leggitt, L; Riley, D (2010)
Exceptionally well-preserved specimens of a new cypridid ostracode (Crustacea), Raepula ira sp. nov., are described from palaeolake sediments of the Middle Miocene Barstow Formation of the Mud Hills, southern California. This is only the second occurrence of exceptionally preserved ostracodes from the Miocene. Based on ages obtained from associated volcanic tuffs the palaeolake sediments were deposited between 16.3 and 15.8 Ma. The ostracodes form one element of a diverse lake community dominated by fairy shrimps, copepods, diatoms, larvae of diving beetles, flies and mosquitoes, and body fossils and ephippia of branchiopods and anomopods. The ostracodes are preserved three dimensionally with their soft anatomy replicated in microcrystalline silica. Submicron-scale details such as sensory setae are preserved, surpassing the resolution of most other ostracode-bearing lagerstätten and allowing their biology to be compared with extant taxa. © 2010 Geological Society of London.